Effect of a workplace-based group training programme combined with financial incentives on smoking cessation: a cluster-randomised controlled trial - Floor A van den Brand, MSc; Gera E Nagelhout, PhD; Bjorn Winkens, PhD; Niels H Chavannes, ProfPhD; Onno C P van Schayck, ProfPhD (Elsevier, 2018)
Summary: Background: Financial incentives are potentially useful tools to aid smoking cessation, but robust evidence to support their efficacy, particularly in combination with other interventions (eg, group counselling), has not been reported. We aimed to investigate whether financial incentives combined with a smoking cessation group training programme (compared with a training programme with no incentives) organised at the workplace would increase 12-month abstinence rates in tobacco-smoking employees with different education and income levels. Methods: This cluster-randomised controlled trial was done in the Netherlands with companies that offer a smoking cessation group training programme to all of their smoking employees. Eligible participants were tobacco-smoking employees and spouses of employees who were at least 18 years of age. Participants in the control group received a weekly 90-min session of smoking cessation group training for 7 weeks at the workplace; in addition to the group training, participants in the intervention group received vouchers for being abstinent (€50 at the end of the training programme, €50 3 months after completion of the programme, €50 after 6 months, and €200 after 12 months). Companies were randomly assigned by an independent research assistant to the intervention group or the control group with a digital randomisation programme, using a biased urn method. The primary outcome was carbon monoxide-validated continuous abstinence at 12 months. All randomised participants were included in the modified intention-to-treat analyses, with the exception of unavoidable loss (participants who had died or moved to an untraceable address (according to the Russell Standard), and in the sensitivity analyses, except the complete case analysis, which included only participants for whom all variables included in the model were not missing. This study is registered with the Dutch Trial Register, number NTR5657. Findings: Between March 1, 2016, and March 1, 2017, 61 companies with 604 participating smokers were enrolled. 31 companies (319 smokers) were randomly assigned to the intervention group and 30 companies (285 smokers) to the control group. 12 months after finishing the smoking cessation programme, the proportion of individuals abstaining from smoking in the intervention group was significantly higher than that in the control group (131 [41%] of 319 vs 75 [26%] of 284; adjusted odds ratio 1·93, 95% CI 1·31-2·85, p=0·0009; adjusted for education level, income level, and Fagerström score). Interpretation: Financial incentives in addition to a smoking cessation group training programme can significantly increase long-term smoking abstinence. The results of the current study could motivate employers to facilitate a workplace smoking cessation programme with financial incentives to help employees to quit smoking. Funding: Dutch Cancer Society.